Peran Kepemimpinan dalam Membentuk Kinerja Kerja Pustakawan di Lingkungan Akademik - Olanike Faith Mesagan (Journal of Education and Teaching (JET), 2024)
The role of librarians within academic institutions has garnered increasing attention due to their important position in facilitating information access and knowledge dissemination. Therefore, the study focused on librarians’ leadership style as correlate of job performance among academic librarians in southwest Nigeria. Correlation design was used with population of 84 librarians. A stratified random sampling technique was used to select the respondents. Mean score ( ), standard deviation (SD), and regression was used for data analysis. The findings indicate a high prevalence of laissez-faire leadership style, a weak positive correlation between laissez-faire leadership and job performance, a moderate relationship between instructional leadership and job performance, and a weak positive relationship between servant leadership style and job performance. Suggestions include create a supportive work environment that encourages creativity, recognizes employees' achievements, prioritizing styles that promote accountability, increase productivity, and improve communication channels. Implementing motivating methods to encourage personnel and enhance their output, providing regular training, and prioritizing their well-being will lead to increased job satisfaction and organizational productivity in the long term.